AKTIVITAS SABUN PADAT EKSTRAK KULIT BUAH APEL (Malus Domestica) TERHADAP Staphylococcus aureus - Zuniarto, Ahmad Azrul; pandanwangi, Siti; Nopitasari, Sindi; Khalifah, Tria Incky (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Soap is a type of skin cleansing agent, suitable for removing various types of dirt and bacteria on the skin. Apple peel waste contains more active ingredients than the fruit. The aim was to determine the antibacterial activity of apple bark (Malus domestica) soap extract against Staphylococcus aureus and determine the optimal concentration to inhibit bacterial growth. The research method used uses laboratory experimental research methods. The measurement method is the diffusion test. This research includes collecting plant materials, making simplicia, making extracts, phytochemical screening, making bar soap, formulating evaluation testing, and testing bar soap formulations from apple peel extract (Malus domestica) against Staphylococcus aureus. The soap resulting from leather waste extraction consists of concentrations of 15%, 20% and 25%, basic ingredients for soap, bar soap and disinfectant soap brand there is no real difference. These results indicate that bar soap containing apple peel extract (Malus domestica) at a concentration of 25% is most effective against Staphylococcus aureus. The conclusion of this study shows that bar soap containing apple peel extract (Malus domestica) has antibacterial activity against Staphylococcus aureus.